Strategi Promosi Festival Kebudayaan Antarabangsa Tawau - Ernawati, Ahmad (Universiti Malaysia Sarawak (UNIMAS), 2016)
Tawau International Cultural Festival portrays a total of 25 different types of ethnicity within the district of Tawau itself and the combination of countries from BIMP-EAGE. BIMP-EAGE countries stand for Brunei, Indonesia, Malaysia, and Philippines. The aim ofthis project is to affirm the existing promotion strategy. The main element used in promoting are watercolour technique. Medium proposed for advertising includes printed media, social media channel, commercial television and ambience advertisement.